Camelobaetidius francischettii: a new species of Baetidae (Ephemeroptera) from Brazil - Salles, F. F.; Andrade, M. B.; Da-Silva, E. R. (Zootaxa, 2005)
Camelobaetidius francischettii, new species, is described based on nymphs collected from Alagoas and Rio de Janeiro states, Northeastern and Southeastern Brazil, respectively. The species can be distinguished from the other described species of the genus by the following combination of characters: (1) segment 2 of labial palp with distomedial process rounded and strongly produced; (2) fore femora with prominent protuberance; (3) fore tibia with indentation at apex; (4) ventral margin of fore femur and fore tibia entirely scattered with spines; (5) tarsal claws with 34 to 37 denticles; (6) small thoracic gill at the base of fore coxae; (7) prosternum with a single, medial protuberance; (8) paraprocts with ca. 22 marginal small spines; and (9) terminal filament about as long as the length of the 10 th abdominal segment.